Keunggulan Petahana dalam Pemilihan Legislatif di Kabupaten Manggarai Tahun 2024 : Studi Tentang Kemenangan Petahana Paulus Peos di Dapil I - Matius A. Sabto Galus; Esrah D. N. A. Benu; Stefanus Triadmaja; Rex Tiran (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
This study aims to analyze the incumbent’s advantage in the 2024 Manggarai Regency Legislative Election with a case study of Paulus Peos’ victory in Electoral District I. The theory used is David R Mayhew’s approach. The method used is a descriptive qualitative approach through interviews, observation, and documentation. The results of the study show that Paulus Peos’ success in retaining his legislative seat for four consecutive terms was supported by three main factors, namely name recognition (advertising), credit claiming, and position taking. Through advertising, Paulus Peos built a positive image and connection with the community; through credit claiming, Paulus Peos emphasized his contributions to various development programs; and through position taking, Paulus Peos demonstrated his commitment to the aspirations of the people. These three factors fostered strong voter loyalty and trust, proving that the incumbent’s advantage stemmed not only from his political position but also from his ability to build social relationships and his consistent performance in serving the community.